RELATIONSHIP BETWEEN CONSUMER KNOWLEDGE AND FRESH COW MILK CONSUMPTION IN WEST SUMATERA - Sillia, Nova; Hellyward, James; Noer, Melinda (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
Consumer knowledge builds a consumer perception. This perception can influence consumer preferences and behavior. Previous research has explained the relationship between consumer knowledge and consumption, primarily focusing on product knowledge. In contrast, consumer knowledge is not only about products knowledge but also purchasing and usage knowledge. This study aims to identify consumer knowledge about the product, purchase, and usage of fresh cow milk and analyze its relationship with the level of consumption of fresh milk. Consumer product knowledge variables are differences and benefits of the product. Consumer purchasing knowledge variables are price and place of purchasing. Consumer usage knowledge variables are storage and post-storage processing. Consumer knowledge level was analyzed using the quantitative descriptive method, and the relationship between knowledge and consumption level was analyzed using Chi-square analysis. This study explains that consumers have excellent purchasing knowledge, followed by product knowledge and usage knowledge. It means that increasing consumer knowledge is needed to increase the product, purchasing, and usage knowledge. This study also explains that fresh cow milk consumption depends on consumer product knowledge.